PENGARUH PENGAJARAN REMEDIAL TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN (PAK) PADA SISWA KELAS XI SMK NEGERI 1 LAGUBOTI TAHUN PEMBELAJARAN 2019/2020 - Nababan, Tulus Delima Meilita (IAKN Tarutung, 2020)
This study aims to determine the level of remedial teaching achievement, the level of learning outcomes before remedial and the level of PAK learning outcomes of students in SMK Negeri 1 Laguboti in the 2019/2020 academic year, as well as to determine the positive and significant influence between remedial teaching on the learning outcomes of PAK XI grade students of XI SMK Negeri 1 Laguboti 2019/2020 academic year. The hypothesis of this study is: there is a positive and significant influence of remedial teaching on the learning outcomes of PAK XI grade students of SMK Negeri 1 Laguboti 2019/2020 academic year. Researchers used quantitative inferential statistical research. The population in this study amounted to 105 people and a sample of 51 people. The research instrument used was a closed questionnaire and tests.The conclusions of this study were the level of remedial teaching achievement of 64.924% with a good scale range, the level of achievement of learning outcomes before remedial to students amounted to 59.51 with the completion criteria or 70, and the level of learning outcomes after learning remedial for students is 82.12 with naotas criteria or 70. And the positive relationship test results obtained value of 0.418 tute 0.297. The result of simple linear equation is Y-62.239 + 0.303, with tnne lutei value (3,260 1,684) and futur fme value (10,626 4,08) so that it can be collected that the hypothesis is accepted.Keywords: Remedial Teaching, Student PAK Learning outcomes